Associates’ heterogeneity and capital structure of the non-financial cooperatives in Colombia - Hernández Salazar, Giovanni Andrés; Olaya Pardo, Ana María; Torres Guevara, Luz Elba (REVESCO. Revista de Estudios Cooperativos, 2020)
This research aims to quantitatively prove the existence of a positive and significant relationship between the socio-economic diversity and the heterogeneity of the commitment of the associates with the debt structure of the cooperative. Socio-economic information of the associates and the financial statements discriminated to 6 accounting digits reported to the Confederation of Cooperatives of Colombia (Confecoop) during the 2009-2013 period, models of causal inference pairing were estimated. It is concluded that there is a positive and significant relationship between the socio-economic heterogeneity of the associates and the level of short and long-term debt of non-financial cooperatives in Colombia. These results are mainly explained by the associates’ desire to protect assets, soften consumption and mitigate risk.
Keywords: Non Profit Organization; Matching Models; Diversity; Finance; Debt Structure.